Hymns, homilies and hermeneutics in Byzantium (Leiden ; Boston)
x, 247 sayfa
Keywords: “The essays in Hymns, Homilies and Hermeneutics explore the literature of Byzantine liturgical communities and provide a window into lived Christianity in this period. The liturgical performance of Christian hymns and sermons creatively engaged the faithful in biblical exegesis, invited them to experience theology in song, and shaped their identity. These sacred stories, affective scripts and salvific songs were the literature of a liturgical community - hymns and sermons were heard, and in some cases sung, by lay and monastic Christians throughout the life of Byzantium. In the field of Byzantine studies there is a growing appreciation of the importance of liturgical texts for understanding the many facets of Byzantine Christianity: we are in the midst of a liturgical turn. This book is a timely contribution to the emerging scholarship, illuminating the intersection between liturgical hymns, homiletics and hermeneutics.“ --